2022
DOI: 10.3102/00346543211073188
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Model of Statistical Learning and Reading: Evidence From a Meta-Analysis

Abstract: A compelling demonstration of implicit learning is the human ability to unconsciously detect and internalize statistical patterns of complex environmental input. This ability, called statistical learning, has been investigated in people with dyslexia using various tasks in different orthographies. However, conclusions regarding impaired or intact statistical learning in dyslexia remain mixed. This study conducted a systematic literature search of published and unpublished studies that compared statistical lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 126 publications
0
42
0
Order By: Relevance
“…Previous behavioral studies have demonstrated that statistical learning—the ability to involuntarily extract and encode relational patterns of environmental input—plays a critical role in reading acquisition (for a review, see Lee et al, 2022 ). This is partly because many orthographies contain myriad statistical patterns that can be detected and learned by young children through mere repeated exposure (e.g., Frost et al, 2013 ; Treiman and Kessler, 2022 ).…”
mentioning
confidence: 99%
“…Previous behavioral studies have demonstrated that statistical learning—the ability to involuntarily extract and encode relational patterns of environmental input—plays a critical role in reading acquisition (for a review, see Lee et al, 2022 ). This is partly because many orthographies contain myriad statistical patterns that can be detected and learned by young children through mere repeated exposure (e.g., Frost et al, 2013 ; Treiman and Kessler, 2022 ).…”
mentioning
confidence: 99%
“…Some new theoretical frameworks have been proposed to explain statistical learning impairment in dyslexia. For example, a multicomponent memory network, referred to as the Statistical Learning and Reading (SLR) model (Lee et al, 2022), represents a domain-general system that consists of a short-term memory subsystem, an explicit declarative long-term memory subsystem, and an implicit procedural long-term memory subsystem. The two long-term memory subsystems are distinguishable in terms of the attentional demands required for encoding and storage of information, with more controlled attention (i.e., a top-down selective attention to learning stimuli) than automatic attention (i.e., a bottom-up involuntary attention to salient stimuli) needed in the explicit declarative subsystem, and, conversely, more automatic attention than controlled attention needed in the implicit procedural subsystem.…”
Section: Discussionmentioning
confidence: 99%
“…Dyslexia might therefore reflect deficits in the learning of statistical regularities in the environment more generally. A recent meta-analysis of 49 empirical studies (Lee et al, 2022) concluded that dyslexic readers have domaingeneral and language-independent statistical learning deficits. Banai & Ahissar (2018) reported that problems with picking up sound statistics occur in about 50% of those with dyslexia.…”
Section: Visual Learning and Temporal Context In Perceptionmentioning
confidence: 99%
“…They could also be a manifestation of a more general deficit in procedural learning (Gabay et al, 2015;Nicolson et al, 2010) or reflect lessened effects of recent perceptual information or top-down expectations on current perceptual representations due to dysfunction in rapid neural plasticity (Ahissar, 2007;Beach et al, 2022;Perrachione et al, 2016). Also, some studies have not found any problems at all with visual statistical learning in dyslexic readers (e.g., (van Witteloostuijn et al, 2019(van Witteloostuijn et al, , 2021; see also discussion in Schmalz et al, 2017) but a recent meta-analysis by Lee et al (2022) does indicate that the problem is real. It is also possible that people with dyslexia show atypical predictive processing in visual statistical learning paradigms as measured neurally that does not always manifest in overt behavior (Singh et al, 2018).…”
Section: Visual Learning and Temporal Context In Perceptionmentioning
confidence: 99%